2020
DOI: 10.5812/ijpbs.100930
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Persian Version of Structured Clinical Interview for DSM-5-Research Version (SCID-5-RV): A Diagnostic Accuracy Study

Abstract: Background: The structured clinical interview for DSM-5 has recently been revised to reflect the new findings in the diagnostic criteria of psychological disorders. Objectives: The present study aimed to evaluate the reliability and validity of the Persian translation of structured clinical interview for diagnostic and statistical manual of mental disorders-fifth edition (DSM-5)-research version (SCID-5-RV) on Iranian adult population. Methods: In the current diagnostic accuracy study a total of 305 clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 21 publications
0
37
4
Order By: Relevance
“…The decrease in BDRS mean score is attributable to conventional medication therapy in the control group and SEDP in the intervention group. Previous studies highlighted that the positive effects of psychoanalytic therapies appear over time, usually after three months (21,22), because changes in lifestyle behaviors usually need time (23). However, our findings showed that SEDP had significant positive effects on BDRS mean score at three and six months after the intervention and the between-group difference respecting the BDRS mean score was statistically significant at these two time points.…”
Section: Discussioncontrasting
confidence: 70%
“…The decrease in BDRS mean score is attributable to conventional medication therapy in the control group and SEDP in the intervention group. Previous studies highlighted that the positive effects of psychoanalytic therapies appear over time, usually after three months (21,22), because changes in lifestyle behaviors usually need time (23). However, our findings showed that SEDP had significant positive effects on BDRS mean score at three and six months after the intervention and the between-group difference respecting the BDRS mean score was statistically significant at these two time points.…”
Section: Discussioncontrasting
confidence: 70%
“…The validity and reliability of the original version have been proven in several studies and the calculated kappa value showed excellent agreement for substance use disorders ( Osório et al, 2019 , Shankman et al, 2018 ). Furthermore, the validity and reliability study of Persian version of the SCID-5 was established in an Iranian sample and good internal consistency (0.95–0.99), test–retest reliability (0.60–0.79), and Kappa reliability (0.57–0.72) have been reported ( Mohammadkhani, Forouzan, Hooshyari, & Abasi, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…SCID-5: The Structured Clinical Interview for DSM-5 (SCID-5) was administered by psychiatrists or clinical psychologists to make a main diagnostic in axis I or axis 2 disorders ( 19 ). The Persian version of SCID-5 has been prepared across a psychometric accuracy study with appropriate validity indicators ( 20 ). The information from this interview was used for 2 purposes: First, as a criterion to enter the research as a participant; Second, to check MCMI-IV criteria validity in related scales.…”
Section: Methodsmentioning
confidence: 99%